Autoimmune rheumatic diseases (2014)
The term autoimmune rheumatic diseases (ARDs) encompasses a heterogeneous group of conditions characterized by joint involvement along with a wide spectrum of systemic manifestations. The most common ARDs are rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Nevertheless, all these conditions share similar pathophysiological mechanisms [1, 2] and a common risk of developing a process of accelerated atherosclerosis [3]. In this regard, in this special issue J. Amaya-Amaya and colleagues discussed the mechanisms associated with the increased risk of cardiovascular disease (CVD) in patients with autoimmune diseases. These authors emphasize the relevance of the CVD in rheumatic conditions and its connection with inflammation and autoimmunity. They also highlight the need of a more aggressive management of these conditions, both of disease activity and classic cardiovascular risk factors. A good example of accelerated atherosclerosis in the setting of an ARD is SLE, in which endothelial dysfunction, an early step in the atherogenesis process, is observed before cardiovascular events can occur. With respect to this, A. Mak and N. Y. Kow performed a comprehensive review of the mechanisms that are involved in endothelial damage.These authors focused on the factors involved in endothelial damage and repair and, therefore, in the development of CVD in patients with SLE. They discussed the relevant role of factors such as type 1 interferon, proinflammatory cytokines, inflammatory cells, immune complexes, costimulatory molecules, neutrophils extracellular traps, lupus-related autoantibodies, oxidative stress, and dyslipidemia that along with the aberrant function of the endothelial progenitor cells lead to endothelial dysfunction and increased susceptibility to develop CVD in patients with SLE. Based on these lines of evidence, the authors’ claim is in favor of early intervention at the preclinical stage of atherogenesis in these patients.